Large reduction in thermal conductivity for SiGe alloy nanowire wrapped with a Ge nanoparticle-embedded SiO2 shell. (16th June 2016) - Lee, Jong Woon; Lee, Junho; Jung, Su-Ho; Jang, Yamujin; Choi, Byoung Lyong; Yang, Cheol-Woong; Whang, Dongmok; Lee, Eun Kyung
Abstract: We demonstrate silicon germanium (SiGe) alloy nanowires (NWs) with Ge nanoparticles (GeNPs) embedded in a SiO2 shell as a material for decreasing thermal conductivity. During thermal oxidation of SiGe NWs to form SiGe–SiO2 core–shell structures, Ge atoms were diffused into the SiO2 shell to relax the strain in the SiGe core, and agglomerated as a few nanometer-sized particles. This structure leads to a large reduction in thermal conductivity due to the GeNP–phonon interaction, while electrical conductivity is sustained because the core of the SiGe alloy NW provides a current path for the charged carriers. The thermal conductivity of the SiGe alloy NWs wrapped with a GeNP-embedded SiO2 shell is 0.41 W m −1 K −1 at 300 K.